2020
DOI: 10.1111/bjhp.12488
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality and blunted cardiovascular stress reactivity: Role of task engagement

Abstract: Objective. The underlying mechanisms for linking Type D personality to cardiovascular stress reactivity remain unknown. The present study explored the possible mediating role of cognitive appraisals of stress and/or motivational levels involved in stress in the association between Type D personality and cardiovascular stress reactivity.Design. Cross-sectional.Methods. Chinese version of Type D Scale-14 was administered to 154 undergraduate students who underwent psychosocial stress during which the physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 73 publications
(105 reference statements)
0
7
0
2
Order By: Relevance
“…Extensive study details including significant effects, the operationalization of Type D personality, stress tasks, and statistical approaches are provided in . In brief, four studies linked Type D personality to lower cardiovascular reactivity (Kelly-Hughes et al, 2014; Lü & Yao, 2021; O’Leary et al, 2013; O’Riordan, Howard, & Gallagher, 2022), one study found Type D to be associated with greater reactivity (Williams et al, 2009), and two studies linked Type D personality to both higher and lower cardiovascular reactivity, depending on the parameter of focus (Howard et al, 2011; O’Riordan, Howard, Brown, & Gallagher, 2020). Furthermore, three studies found either sex or the social salience of the experimental stressor (or both) to moderate the association between Type D and cardiovascular reactivity (Bibbey et al, 2015; Gramer et al, 2018; O’Riordan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Extensive study details including significant effects, the operationalization of Type D personality, stress tasks, and statistical approaches are provided in . In brief, four studies linked Type D personality to lower cardiovascular reactivity (Kelly-Hughes et al, 2014; Lü & Yao, 2021; O’Leary et al, 2013; O’Riordan, Howard, & Gallagher, 2022), one study found Type D to be associated with greater reactivity (Williams et al, 2009), and two studies linked Type D personality to both higher and lower cardiovascular reactivity, depending on the parameter of focus (Howard et al, 2011; O’Riordan, Howard, Brown, & Gallagher, 2020). Furthermore, three studies found either sex or the social salience of the experimental stressor (or both) to moderate the association between Type D and cardiovascular reactivity (Bibbey et al, 2015; Gramer et al, 2018; O’Riordan et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A total of nine studies examined the continuous Type D interaction term (NA × SI; Allen et al, 2019a; Gramer et al, 2018; Howard et al, 2011; Kelly-Hughes et al, 2014; Lü & Yao, 2021; O’Leary et al, 2013; O’Riordan et al, 2019; O’Riordan, Howard, Brown, & Gallagher, 2020; O’Riordan, Howard, & Gallagher, 2022). Four studies confirmed significant categorical Type D effects in follow-up analyses using the continuous Type D interaction term (NA × SI; Gramer et al, 2018; Howard et al, 2011; O’Leary et al, 2013; O’Riordan, Howard, Brown, & Gallagher, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations